Anxiety, Confidence, And Cohesiveness In Students Of The Special Class Of Sports Football - Ginanjar, Afan; Riansyah, Riansyah; Siahaan, Derry Renanda Putra; Damayanti, Nadia Fadilla (STAMINA, 2025)
This study aims to identify the level of anxiety, confidence, and cohesiveness in students of Special Sports Class (KKO) at SMA Negeri 1 Kroya, Cilacap Regency. These three psychological aspects are the foundation in the formation of students' character in the field and outside the field, but they are not taken seriously. This research is important as the first step in forming psychological aspects in students to be better. This research is a descriptive research. The method used is a survey. The data collection instrument uses a questionnaire. The sample in this study is 20 students of the Special Sports Class of the football branch. The data analysis technique uses quantitative descriptive analysis presented in the form of percentages. The results of the study show that; (1) The anxiety level of students of the Special Sports Class of football at SMA Negeri 1 Kroya in the very low category of 10% amounting to 2 students, low 30% amounting to 6 students, sufficient 15% amounting to 3 students, high 40% amounting to 8 students, and very high 5% amounting to 1 student; (2) The level of confidence in the very low category is 5% amounting to 1 student, low 25% amounting to 5 students, sufficient 50% amounting to 10 students, high 10% amounting to 2 students, and very high 10% amounting to 2 students; (3) The level of cohesiveness in the very low category is 5% amounting to 1 student, low 15% amounting to 3 students, sufficient 50% amounting to 10 students, high, 25% amounting to 5 students, and very high 5% amounting to 1 student